Dual neutralisation of interleukin-17A and interleukin-17F with bimekizumab in patients with active ankylosing spondylitis: results from a 48-week phase IIb, randomised, double-blind, placebo-controlled, dose-ranging study. Issue 5 (6th April 2020) - van der Heijde, Désirée; Gensler, Lianne S; Deodhar, Atul; Baraliakos, Xenofon; Poddubnyy, Denis; Kivitz, Alan; Farmer, Mary Katherine; Baeten, Dominique; Goldammer, Nadine; Coarse, Jason; Oortgiesen, Marga; Dougados, Maxime
Abstract : Objectives: Bimekizumab selectively neutralises both interleukin (IL)-17A and IL-17F. We report efficacy and safety in a phase IIb dose-ranging study in patients with active ankylosing spondylitis (AS). Methods: Adults with AS (fulfilling modified New York criteria) were randomised 1:1:1:1:1 to bimekizumab 16 mg, 64 mg, 160 mg, 320 mg or placebo every 4 weeks for 12 weeks (double-blind period). At week 12, patients receiving bimekizumab 16 mg, 64 mg or placebo were re-randomised 1:1 to bimekizumab 160 mg or 320 mg every 4 weeks to week 48; other patients continued on their initial dose (dose-blind period). The primary end point was Assessment of SpondyloArthritis international Society (ASAS) 40 response at week 12 (non-responder imputation (NRI) for missing data). Results: 303 patients were randomised: bimekizumab 16 mg (n=61), 64 mg (n=61), 160 mg (n=60), 320 mg (n=61) or placebo (n=60). At week 12, significantly more bimekizumab-treated patients achieved ASAS40 vs placebo (NRI: 29.5%–46.7% vs 13.3%; p<0.05 all comparisons; OR vs placebo 2.6–5.5 (95% CI 1.0 to 12.9)). A significant dose-response was observed (p<0.001). The primary end point was supported by all secondary efficacy outcomes. At week 48, 58.6% and 62.3% of patients receiving bimekizumab 160 and 320 mg throughout the study achieved ASAS40, respectively (NRI); similar ASAS40 response rates were observed in re-randomised patients. During the double-blind period, treatment-emergent adverse events occurred in 26/60 (43.3%) patients receiving placebo and 92/243 (37.9%) receiving bimekizumab. Conclusions: Bimekizumab provided rapid and sustained improvements in key outcome measures in patients with active AS, with no unexpected safety findings versus previous studies. Trial registration number: NCT02963506 .